Pex20p functions as the receptor for non‐PTS1/non‐PTS2 acyl‐CoA oxidase import into peroxisomes of the yeast Yarrowia lipolytica. (27th May 2019) - Chang, Jinlan; Rachubinski, Richard A.
Abstract: Most soluble proteins targeted to the peroxisomal matrix contain a C‐terminal peroxisome targeting signal type 1 (PTS1) or an N‐terminal PTS2 that is recognized by the receptors Pex5p and Pex7p, respectively. These receptors cycle between the cytosol and peroxisome and back again for multiple rounds of cargo delivery to the peroxisome. A small number of peroxisomal matrix proteins, including all six isozymes of peroxisomal fatty acyl‐CoA oxidase (Aox) of the yeast Yarrowia lipolytica, contain neither a PTS1 nor a PTS2. Pex20p has been shown to function as a co‐receptor for Pex7p in the import of PTS2 cargo into peroxisomes. Here we show that cells of Y. lipolytica deleted for the PEX20 gene fail to import not only the PTS2‐containing protein 3‐ketoacyl‐CoA thiolase (Pot1p) but also the non‐PTS1/non‐PTS2 Aox isozymes. Pex20p binds directly to Aox isozymes Aox3p and Aox5p, which requires the C‐terminal Wxxx(F/Y) motif of Pex20p. A W411G mutation in the C‐terminal Wxxx(F/Y) motif causes Aox isozymes to be mislocalized to the cytosol. Pex20p interacts physically with members of the peroxisomal import docking complex, Pex13p and Pex14p. Our results are consistent with a role for Pex20p as the receptor for import of the non‐PTS1/non‐PTS2 Aox isozymes into peroxisomes. Abstract : Most peroxisomal matrix proteins contain a C‐terminal PTS1 or N‐terminal PTS2 targeting signal recognized by cytosolic receptors Pex5p and Pex7p, respectively. However, isozymes of peroxisomal fatty acyl‐CoA oxidase (Aox) of the yeast Yarrowia lipolytica lack both PTS1 and PTS2. Pex20p was shown to function as a co‐receptor for Pex7p. We now show that Pex20p also functions as the import receptor for non‐PTS1/non‐PTS2 Aox3p and Aox5p into peroxisomes and interacts with Pex13p and Pex14p, two components of the peroxisomal docking complex, which together with the RING complex (Pex2p, 10p and 12p) forms the importomer for matrix translocation into the peroxisome.